Resolving the pulsations of the subdwarf B star KPD 2109 + 4401 - Zhou, A. -Y.; Reed, M. D.; Harms, S.; Terndrup, D. M.; An, D.; Zola, S.; Gazeas, K. D.; Niarchos, P. G.; Ogloza, W.; Baran, A.; Wolf, G. W. (Monthly Notices of the Royal Astronomical Society, 2006)
We present the results of extensive time-series photometry of the pulsating subdwarf B star KPD 2109 + 4401. Our data set consists of 29 data runs with a total length of 182.6h over 31d, collected at five observatories in 2004. These data comprised high signal-to-noise ratio observations acquired with larger telescopes and wider time-coverage observations obtained with smaller telescopes. They are sufficient to resolve the pulsation structure to 0.4 μHz and are the most extensive data set for this star to date. With these data, we identify eight pulsation frequencies extending from 4701 to 5481μHz, corresponding to periods of 182-213s. The pulsation frequencies and their amplitudes are examined over several time-scales with some frequencies showing amplitude variability.
Keywords: Astrophysics; stars: individual: KPD 2109 + 4401-stars: oscillations-subdwarfs-stars: variables: other